Ez nem szemét, hanem egy kutatásnak a forrása - Kresalek, Dávid; Soponyai, Dóra (Hungary, 2015)
A group of researchers at the Hungarian Ethnographic Museum are using items left behind by refugees at the Serbian-Hungarian border as a source of information on immigrant culture.
Verzio Film Festival Submission
Keywords: Documentary films